Relevance of Education and Challenges in the Job Market: Results of Tracer Study of Graduates of 2022 - Istaryatiningtias, Istaryatiningtias; El Khuluqo, Ihsana (Journal of English Language and Education, 2025)
This study aims to evaluate the relevance of master's degree (S2) education to the challenges in the workforce through a tracer study of graduates from the year 2022. A tracer study is a survey conducted to gather data on graduates' perceptions regarding the alignment of their S2 education with job requirements and career development. Data were collected through questionnaires distributed to 72 graduates, with a response rate of 100%. The results show that all respondents were employed before starting their S2 education. Of the 52 respondents who answered, 43 (82.7%) stated that their S2 education was aligned with their job requirements and assisted in career development. Additionally, 26 (50%) graduates felt that higher-level education was needed for more advanced career positions. Meanwhile, 3 (5.8%) respondents indicated that their current jobs only required lower-level education. These findings indicate that S2 education plays a significant role in professional career development, although there is a noted need for further education at higher levels for certain positions. Recommendations include enhancing cooperation between educational institutions and industries to align curricula with specific job requirements and providing advanced education programs relevant to professional career demands